Effect of malt and sugar cane bagasse in nutrient retention in extensive green roof substrates (Research, Society and Development, 2021)
This study aimed to evaluate the quality of runoff water of experimental units of green roofs containing substrates added of low-cost adsorbent materials, such as malt bagasse (M) and sugar cane bagasse (C). Each experimental unit was built with a geotextile membrane, a substrate, and vegetation (Arachis repens). The substrates M and C were compared with a control substrate (CON) widely used commercially. The experiment was developed in two steps: manual irrigation and rainfall. The quality of the runoff water from the experimental units was analyzed using the parameters real color, turbidity, total solids, pH, electric conductivity, nitrate , phosphate  and sulphate The substrates had relevant effects in the concentrations of , and , being that the substrate C had better performance retention. Water distribution and impact in the experimental units presented differences regarding nutrients transport, with less lixiviate in the manual irrigation step. The results suggest that using sugar cane bagasse in green roofs to improve runoff quality is promising.